The Effect of Project Based Learning Integrated STEM to Increase Science Process Skill - Septina Severina Lumbantobing; Faradiba Faradiba; Diaz Jubairy Prabowo; Manogari Sianturi; Taat Guswantoro (Department of Physics Education, Universitas Mataram, 2022)
This research aims to determine the effect of project-based learning integrated with the STEM method on the greenhouse effect and global warming on science process skills of class XI of the MIPA program in Senior High School in 9 Jakarta. This research is experimental research with two groups. Class control using discovery learning and class experiment using PJBL integrated with STEM. The instrument is a multiple-choice test with as many as 20 questions that use science process skills indicators. Analysis of this research data using the independent sample t-test was used to see the effect of the learning model on the science process skills, and the results obtained showed a significant effect. From the results of the analysis data, there is an effect of PjBL learning integrated STEM method to increase science process skills of students of class XI. Applying project-based learning integrated with STEM dramatically improves students' abilities, especially in observing, applying and conducting experiments. For the questionnaire students' responses to the implementation of the learning model, more than 80% of students were becoming more motivated in learning, more help understanding the subject matter, and could improve their problem-solving abilities.